Structure of the JET edge radial electric field in He and D plasmas. (22nd October 2021) - Silva, C.; Solano, E.R.; Hillesheim, J.C.; Delabie, E.; Aleiferis, S.; Birkenmeier, G.; Gil, L.; Giroud, C.; Litherland-Smith, E.; Morales, R.B.; Nina, D.; Silva, A.; et al.
Abstract: Perpendicular velocity, v ⊥, measurements have been obtained in JET experiments designed to investigate the underlying mechanisms influencing the L–H power threshold. L–H transitions were induced by using both NBI and ICRH in deuterium and helium plasmas. The v ⊥ profile in the low density branch of the L–H transition has a modest or even no well and a marked peak near the separatrix in NBI heated discharges for both D and He plasmas, with a sharper SOL peak for He plasmas. As the line-averaged density increases, the SOL v ⊥ peak decreases, in agreement with the modifications in the electron temperature profile at the divertor target, while the v ⊥ well becomes deeper. Nevertheless, even in the high density branch, a shallow v ⊥ well is found at the L–H transition, v ⊥ ∼ 1–2 km s −1, which is lower by a factor of about two than the contribution from the diamagnetic term. No evidence for the existence of a critical value in v ⊥ is found at JET, particularly for helium plasmas. This may be explained by the existence of an edge toroidal flow relevant mainly at low density where the power threshold is high. In addition, no significant change in the edge v ⊥ is measured preceding the L–H transition.